2010
DOI: 10.1093/ije/dyq217
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of information-driven HIV/AIDS policies in China

Abstract: Background As China continues to commit to universal access to HIV/AIDS prevention, treatment and care services, its HIV/AIDS policies have become increasingly information driven. We review China’s key national-level HIV/AIDS policies and discuss policy gaps and challenges ahead.Methods We conducted a desk review of key national-level policies that have had a major impact on China’s HIV/AIDS epidemic, and examined recent epidemiological data relevant to China’s HIV response.Results National-level policies that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
91
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(93 citation statements)
references
References 12 publications
1
91
0
1
Order By: Relevance
“…These two groups were therefore combined. With regard to antiretroviral therapy, the Four Free and One Care policy 9 in China provides free antiretroviral therapy to PLWHA if their CD4+ T lymphocyte level is lower than 350 cells/mm 3 . Therefore, this was assessed on the basis of the receipt of any type of antiviral treatment from the provincial CDC.…”
Section: Measurements Of Psychological Well-beingmentioning
confidence: 99%
See 1 more Smart Citation
“…These two groups were therefore combined. With regard to antiretroviral therapy, the Four Free and One Care policy 9 in China provides free antiretroviral therapy to PLWHA if their CD4+ T lymphocyte level is lower than 350 cells/mm 3 . Therefore, this was assessed on the basis of the receipt of any type of antiviral treatment from the provincial CDC.…”
Section: Measurements Of Psychological Well-beingmentioning
confidence: 99%
“…Studies conducted in foreign countries revealed that nearly half of PLWHA suffered from anxiety disorders and that 20-32% of PLWHA were affected by depressive disorders. [6][7][8] In China, policies such as the 5-Year Action Plans and Four Frees and One Care 9 have been implemented to improve HIV/AIDS prevention, treatment, and care services. These policies have mainly focused on physical health care and not on the psychological health of PLWHA.…”
Section: Introductionmentioning
confidence: 99%
“…There also is encouraging evidence that condoms can be successfully incorporated into comprehensive STI prevention strategies that involve multiple prevention messages, as demonstrated by recent examples from Uganda, 85 Thailand 9 and China. 86 Although the emphasis continues to be placed on developing biomedical interventions (e.g. vaccines, microbicides, circumcision), the male latex condom remains the most effective, most widely available and by far the least expensive prevention method.…”
mentioning
confidence: 99%
“…Methadone: China has a current policy that supports methadone treatment for opioid dependence as a national approach to the HIV/ AIDS epidemic [104]. The national approach to HIV/AIDS is to develop pragmatic solutions to the changing epidemic based on sound scientific information.…”
Section: Peoples Republic Of Chinamentioning
confidence: 99%
“…China's initial response was via a police crackdown on drug use. Incarceration, rehabilitation units with labor or compulsory detoxification were used [104]. However, this strategy did not stop the spread of HIV.…”
Section: Peoples Republic Of Chinamentioning
confidence: 99%